PERBEDAAN TINGKAT DEPRESI ANTARA LANSIA YANG TINGGAL DI PSTW DENGAN LANSIA YANG TINGGAL DI TENGAH KELUARGA - Rima ' Sari; Arneliwati ' '; Sri ' Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Depression is the most often psychiatric disorder occurs in elderly. Residence difference was reposted as predictor of depression in elderly. This study aimed to compare the depression scale between elderly people who lived in nursing home and elderly who lived with family. The research used descriptive analytic design with comparative study. The study was conducted in two population, they are elderly who live in nursing home Khusnul Khotimah Pekanbaru using purposive sampling and in Delima village on 40 elderly using proportional sampling. This study used questionnaire Geriatric Depression Scale defined by Yesavage. The analysis used was univariate using frequency distribution and bivariate analysis using Mann-Whitney. The results of research about depression scale showed that elderly who lived with family have low depression a little more than elderly in nursing home were 32 elderly (80,0%) in family not depressed and mild depression were 21 elderly (52,5%) in nursing home. Based on the statistical tests (Mann-Whitney) results, it is concluded that there is difference of depression scale between elderly people living in nursing home and elderly who lived with family (ρ 0,000 < α 0,05). Based on the result of this study, it is expected for nursing home and community health nursing give a intensive counseling care and running benefit programs to reduce the depression scale of elderly. Keywords: Depression, elderly, family, nursing home